2010
DOI: 10.1021/cm1030975
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of the BiFeO3−LaFeO3System

Abstract: The (1x)BiFeO 3 -xLaFeO 3 system has been investigated and characterized by room-temperature and high-temperature laboratory and synchrotron powder X-ray diffraction, electron diffraction, high-resolution transmission electron microscopy, differential scanning calorimetry, and magnetization measurements. At room temperature, the ferroelectric R3c phase is observed for 0.0 e x e 0.10. The PbZrO 3 -related ffiffi ffi p 2a p  2 ffiffi ffi p 2a p  4a p superstructure (where a p is the parameter of the cubic pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
191
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(225 citation statements)
references
References 36 publications
31
191
3
Order By: Relevance
“…Finally, the GdFeO 3 type P nma structure was reached above x = 0.5. 16 These subtle structural transitions were further corroborated by neutron diffraction experiments where the PbZrO 3 structure with P bam symmetry was observed for Bi 0.82 La 0.18 FeO 3 . Signs of an incommensurate structure with diffraction peaks very similar to P bam was, however, not observed until x = 0.25.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Finally, the GdFeO 3 type P nma structure was reached above x = 0.5. 16 These subtle structural transitions were further corroborated by neutron diffraction experiments where the PbZrO 3 structure with P bam symmetry was observed for Bi 0.82 La 0.18 FeO 3 . Signs of an incommensurate structure with diffraction peaks very similar to P bam was, however, not observed until x = 0.25.…”
Section: Introductionmentioning
confidence: 64%
“…17 However, a more recent study, also employing a combination of synchrotron XRD and ED, reported a total of four structural phases. 16 A single phase R3c structure was reported up to x = 0.1, followed by a mixed phase region for x < 0.18. At this point, a single phase P nam structure of the PbZrO 3 type was observed.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations